FOXC1 is associated with estrogen receptor alpha and affects sensitivity of tamoxifen treatment in breast cancer. (28th December 2016) - Wang, Jinhua; Xu, Yali; Li, Li; Wang, Lin; Yao, Ru; Sun, Qiang; Du, Guanhua
Abstract: FOXC1 is a member of Forkhead box transcription factors that participates in embryonic development and tumorigenesis. Our previous study demonstrated that FOXC1 was highly expressed in triple‐negative breast cancer. However, it remains unclear what is the relation between FOXC1 and ER α and if FOXC1 regulates expression of ER α . To explore relation between FOXC1 and ER α and discover regulation of ER α expression by FOXC1 in breast cancer, we analyzed data assembled in the Oncomine and TCGA, and found that there was significantly higher FOXC1 expression in estrogen receptor‐negative breast cancer than that in estrogen receptor‐positive breast cancer. Overexpression of FOXC1 reduced expression of ER α and cellular responses to estradiol (E2) and tamoxifen in the MCF‐7 FOXC1 and T47D FOXC1 cells, while knockdown of FOXC1 induced expression of ER α and improved responses to estradiol (E2) and tamoxifen in BT549 FOXC1 shRNA and HCC1806 FOXC1 shRNA cells. In addition, overexpression of FOXC1 reduced expression of progesterone receptor (PR), Insulin receptor substrate 1 (IRS1), and XBP1 (X‐Box Binding Protein 1) and significantly reduced luciferase activity caused by E2 using ERE luciferase reporter assay. These results suggested that FOXC1 regulated expression of ER α and affected sensitivity of tamoxifen treatment in breast cancer, and that FOXC1 may be used as a potential therapeutic target in ER α ‐negative breast cancer. Abstract : There was significantly higher FOXC1 expression in estrogen receptor‐negative (ER‐) breast cancer than that in estrogen receptor‐positive (ER+) breast cancer. FOXC1 regulates expression of ER α